Forming material

JP7651852B2Active Publication Date: 2025-03-27SUMITOMO BAKELITE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020209453
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-19
Filing Date
2020-12-17
Publication Date
2025-03-27
Estimated Expiration
2040-12-17

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、優れた強度と耐燃性とが両立される成形材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651852000001
    Figure 0007651852000001
Patent Text Reader

Abstract

To provide a molding material which achieves both excellent strength and flame resistance.SOLUTION: A molding material contains (A) an unsaturated polyester resin, (B) a glass fiber and (C) aluminum hydroxide, in which a content of the component (B) with respect to 100 pts.mass of a resin in the molding material is 50 pts.mass or more and 150 pts.mass or less, a content of the component (C) with respect to 100 pts.mass of the resin in the molding material is 100 pts.mass or more and 200 pts.mass or less, and an average particle diameter d50 of the component (C) is 5 μm or more and 30 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding material. [Background technology]

[0002] Patent Document 1 (JP Patent Publication No. 2010-202812 A) describes a technique relating to an unsaturated polyester resin molding material. The document describes a technique for providing a low-shrinkage unsaturated polyester resin molding material composition that gives off no odor during production, during heat and pressure curing, and at room temperature or at ambient temperature, and that does not emit VOCs (volatile organic compounds) or specific malodorous substances, and a molded article obtained by molding using the molding material, in which the low-shrinkage unsaturated polyester resin molding material composition contains an unsaturated polyester resin, diallyl phthalate, and a low-shrinkage agent made of a styrene-based copolymer having a weight-average molecular weight in a specific range. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-202812 A Summary of the Invention [Problem to be solved by the invention]

[0004] As a result of the inventors' investigation of the techniques described in the above patent documents, it became clear that there is still room for improvement in terms of providing a molding material that combines excellent strength and flame resistance. [Means for solving the problem]

[0005] According to the present invention, (A) unsaturated polyester resin, (B) glass fibers, and (C) aluminum hydroxide, A molding material comprising: The content of the component (B) relative to 100 parts by mass of the resin in the molding material is 50 parts by mass or more and 150 parts by mass or less, The content of the component (C) relative to 100 parts by mass of the resin in the molding material is 100 parts by mass or more and 200 parts by mass or less, The average particle size d of the component (C) 50 is 5 μm or more and 30 μm or less.

[0006] According to the present invention, a molded article can also be obtained by molding the molding material of the present invention. Effect of the Invention

[0007] According to the present invention, it is possible to provide a molding material that has both excellent strength and flame resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described. In addition, unless otherwise specified, the suffix "-" in a numerical range indicates from above to below, and both ends of the numerical range are included. In addition, in this embodiment, the composition may contain each component alone or in combination of two or more kinds.

[0009] (molding material) In this embodiment, the molding material contains the following components (A) to (C). (A) Unsaturated polyester resin (B) Glass fiber (C) Aluminum hydroxide The content of component (B) per 100 parts by mass of resin in the molding material is 50 parts by mass or more and 150 parts by mass or less, and the content of component (C) per 100 parts by mass of resin in the molding material is 100 parts by mass or more and 200 parts by mass or less. The average particle diameter d of component (C) 50 is 5 μm or more and 30 μm or less.

[0010] In this embodiment, the molding material contains the above components (A) to (C), and the contents of components (B) and (C) and the average particle size d of component (C) are 50 Since each of these is within a specific range, it is possible to obtain a molded product that has both excellent strength and flame resistance. Furthermore, according to this embodiment, for example, it is possible to obtain a molded article having excellent moisture resistance. Here, the moisture resistance specifically means hydrolysis resistance. The components of the molding material will be described below with specific examples.

[0011] (Component (A)) Component (A) is an unsaturated polyester resin. Specific examples of unsaturated polyester resins include thermosetting resins obtained by reacting and condensing an unsaturated dibasic acid such as maleic anhydride and a saturated dibasic acid such as phthalic anhydride with glycols, and these resins are usually used in the form of being dissolved in a polymerizable monomer such as styrene.

[0012] More specifically, component (A) may be one or more phthalic acid-based unsaturated polyester resins selected from the group consisting of ortho-type resins obtained by reacting and condensing phthalic anhydride or orthophthalic acid with glycols as the saturated dibasic acid and glycolic acid from the raw materials, iso-type resins obtained by reacting and condensing isophthalic acid with glycols, and para-type resins obtained by reacting and condensing terephthalic acid with glycols. From the viewpoint of improving strength and flame resistance, component (A) is preferably one or more phthalic acid-based unsaturated polyester resins selected from the group consisting of a teretype resin obtained by reacting terephthalic acid with a glycol, and an isotype resin obtained by reacting isophthalic acid with a glycol. Specifically, the glycols herein are one or more compounds selected from the group consisting of ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, and neopentyl glycol, and are preferably neopentyl glycol.

[0013] Component (A) contains, for example, at least one of the above teletype and isotype phthalic acid-based unsaturated polyester resins. Component (A) may also contain the above teletype and isotype phthalic acid-based unsaturated polyester resins. When component (A) contains a teletype and an isotype phthalic acid-based unsaturated polyester resin, the proportion of the isotype is, for example, 40 parts by mass or more, and may also be 50 parts by mass or more, or 55 parts by mass or more, per 100 parts by mass of the total of the teletype and the isotype, and may specifically be less than 100 parts by mass, and may also be, for example, 80 parts by mass or less.

[0014] Other examples of component (A) include unsaturated polyesters obtained by reacting and condensing other dibasic acids with glycols, and chlorinated unsaturated polyesters in which some of the hydrogen atoms have been replaced with chlorine atoms.

[0015] The content of component (A) in the molding material is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, still more preferably 20 mass% or more, and even more preferably 22 mass% or more, based on the entire molding material, from the viewpoint of forming a more stable material and of improving moldability by, for example, making the fluidity of the resin more favorable when melted. From the viewpoint of improving flame retardancy and strength, the content of component (A) in the molding material is preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, and even more preferably 35% by mass or less, based on the total amount of the molding material. This also makes it possible to suppress, for example, an increase in costs.

[0016] (Component (B)) Component (B) is glass fiber. From the viewpoint of improving strength, the average fiber diameter of the glass fibers is preferably 3 μm or more, and more preferably 6 μm or more. From the viewpoint of improving the kneadability during preparation of the molding material, the average fiber diameter of the glass fibers is preferably 30 μm or less, and more preferably 15 μm or less. Here, the average fiber diameter of the glass fibers can be measured by observation with a microscope, and can be determined, for example, by measuring the fiber diameters of 100 glass fibers and calculating the average value.

[0017] From the viewpoint of improving strength, the content of component (B) in the molding material is 50 parts by mass or more per 100 parts by mass of the resin in the molding material, preferably 80 parts by mass or more, more preferably 100 parts by mass or more, even more preferably 120 parts by mass or more, and even more preferably 130 parts by mass or more. In addition, from the viewpoint of improving flame resistance, the content of component (B) in the molding material is 150 parts by mass or less, preferably 145 parts by mass or less, more preferably 140 parts by mass or less, and even more preferably 135 parts by mass or less, per 100 parts by mass of the resin in the molding material.

[0018] Here, "100 parts by mass of resin in the molding material" refers to the total content of component (A) and other resins in the molding material; for example, when the molding material contains only component (A) as the resin, it is 100 parts by mass of component (A); and, for example, when the molding material contains component (A) and diallyl phthalate resin as the resins, it is 100 parts by mass of the total of component (A) and diallyl phthalate resin.

[0019] (Component (C)) Component (C) is aluminum hydroxide. Component (C) is specifically in the form of particles. Average particle size of component (C) d 50 From the viewpoint of achieving both excellent strength and flame resistance, the thickness is 5 μm or more, preferably 6 μm or more, and more preferably 7 μm or more. From the same viewpoint, the average particle size of component (C) d 50 is 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, and even more preferably 10 μm or less. Here, the average particle size of component (C) d50 The particle size distribution of the particles can be measured on a volume basis using a commercially available laser diffraction particle size distribution measuring device (e.g., SALD-7000, manufactured by Shimadzu Corporation). 50 ) can be taken as the average particle size.

[0020] From the viewpoint of improving flame resistance, the content of component (C) in the molding material is 100 parts by mass or more per 100 parts by mass of the resin in the molding material, preferably 105 parts by mass or more, more preferably 110 parts by mass or more, even more preferably 115 parts by mass or more, still more preferably 120 parts by mass or more, and even more preferably 125 parts by mass or more. In addition, from the viewpoint of ensuring favorable fluidity of the resin in the molding material when it is melted, and from the viewpoint of improving the strength of the molded product, the content of component (C) in the molding material is 200 parts by mass or less per 100 parts by mass of the resin in the molding material, preferably 180 parts by mass or less, more preferably 160 parts by mass or less, even more preferably 150 parts by mass or less, and even more preferably 140 parts by mass or less.

[0021] The molding material may contain components other than the components (A) to (C). For example, the molding material may contain a resin other than component (A). More specifically, from the viewpoint of improving hydrolysis resistance, the molding material preferably further contains a diallyl phthalate resin. Examples of the diallyl phthalate resin include one or more types selected from the group consisting of an ortho type using phthalic anhydride or orthophthalic acid, an iso type using isophthalic acid, and a para type using terephthalic acid.

[0022] From the viewpoint of improving hydrolysis resistance, the content of the diallyl phthalate resin in the molding material is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, still more preferably 1.5 mass% or more, even more preferably 3 mass% or more, and still more preferably 6 mass% or more, based on the entire molding material. From the viewpoint of improving moldability, the content of the diallyl phthalate resin in the molding material is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, still more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the entire molding material. This also makes it possible to suppress, for example, an increase in costs.

[0023] In the molding material, the ratio of the diallyl phthalate resin to 100 parts by mass of component (A) is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, still more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more, from the viewpoint of improving hydrolysis resistance. In addition, from the viewpoint of improving moldability, the ratio of diallyl phthalate resin per 100 parts by mass of component (A) in the molding material is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 80 parts by mass or less, even more preferably 70 parts by mass or less, and even more preferably 50 parts by mass or less.

[0024] The molding material preferably further contains an inorganic filler other than components (B) and (C) from the viewpoints of improving other mechanical properties, expressing more preferable electrical properties, and adjusting viscosity. Specific examples of inorganic fillers other than components (B) and (C) include one or more selected from the group consisting of magnesium hydroxide, calcium carbonate, calcined clay, uncalcined clay, wollastonite, talc, silica, diatomaceous earth, alumina, magnesium oxide, barium sulfate, and feldspar.

[0025] From the viewpoint of obtaining more favorable mechanical properties or electrical properties of a molded article or viscosity properties of a molding material, the content of inorganic fillers other than components (B) and (C) is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, even more preferably 1.5 mass% or more, still more preferably 2 mass% or more, and is preferably 8 mass% or less, more preferably 6 mass% or less, even more preferably 5 mass% or less, and even more preferably 4 mass% or less, based on the entire molding material.

[0026] Moreover, from the viewpoint of improving the curing characteristics of the molding material, the molding material preferably contains a curing agent, and more preferably contains one or more curing agents selected from peroxides. Specific examples of peroxides include dicumyl peroxide and tert-butyl peroxide. From the viewpoint of obtaining more preferable curing characteristics, the content of the curing agent in the resin composition is, for example, 0.1 mass% or more, preferably 0.5 mass% or more, and for example, 5 mass% or less, preferably 3 mass% or less, and more preferably 2 mass% or less, relative to the entire molding material.

[0027] The molding material may also contain other additives, specific examples of which include release agents such as stearic acid, calcium stearate, magnesium stearate, carnauba wax, and polyethylene; and colorants such as carbon black. The content of these components in the resin composition is, for example, 0.1 mass% or more, preferably 0.5 mass% or more, and for example, 5 mass% or less, preferably 3 mass% or less, based on the entire molding material.

[0028] Next, a method for producing the molding material will be described. For example, the molding material is prepared by first blending components (A) to (C) and other components in predetermined amounts and premixing them using a ribbon blender, planetary mixer, etc. This is then melt-kneaded using a heated roll, a twin-screw extrusion kneader, etc., and the kneaded mixture is granulated, cooled, and then crushed and classified to obtain the molding material. The molding material may be in the form of particles, for example granules.

[0029] (molded product) The molded product is produced by molding using the molding material of the present embodiment described above. Examples of molding methods for obtaining molded products include injection molding, transfer molding, compression molding, etc. Molding conditions such as temperature, pressure, and molding time can be appropriately adjusted depending on the molding method, molding device, or blending of molding materials.

[0030] In this embodiment, the bending strength of the molded product produced by a transfer molding machine (molding conditions: mold temperature 165°C; curing time 4 minutes) in accordance with JIS-K6911 "General testing methods for thermosetting plastics" is, for example, 140 MPa or more, preferably 145 MPa or more, and may be, for example, 200 MPa or less.

[0031] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Below, examples of reference forms are given. 1. (A) Unsaturated polyester resin, (B) glass fibers, and (C) aluminum hydroxide, A molding material comprising: The content of the component (B) relative to 100 parts by mass of the resin in the molding material is 50 parts by mass or more and 150 parts by mass or less, The content of the component (C) relative to 100 parts by mass of the resin in the molding material is 100 parts by mass or more and 200 parts by mass or less, The average particle size d of the component (C) 50 A molding material having a particle size of 5 μm or more and 30 μm or less. 2. The molding material according to 1., further comprising an inorganic filler other than the components (B) and (C). 3. The molding material according to 1. or 2., wherein the component (A) is one or more phthalic acid-based unsaturated polyester resins selected from the group consisting of teretype resins obtained by reacting terephthalic acid with glycols and isotype resins obtained by reacting isophthalic acid with glycols. 4. A molding material according to any one of 1. to 3., further comprising one or more curing agents selected from the group consisting of peroxides. 5. The molding material according to any one of 1. to 4., further comprising a diallyl phthalate resin. 6. The molding material according to 5., wherein the content of the diallyl phthalate resin is 20 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the component (A). EXAMPLES

[0032] Hereinafter, the present embodiment will be described in detail with reference to examples and comparative examples. Note that the present embodiment is not limited to the descriptions of these examples.

[0033] (Examples 1 to 8, Comparative Examples 1 to 3) (Preparation of Resin Composition) The raw materials were mixed according to the composition shown in Table 1, premixed, melt-kneaded with a heating roll at 90° C. for 5 minutes, cooled, and pulverized to obtain a granular molding material.

[0034] Details of each component in Table 1 are as follows. Unsaturated polyester resin 1: (A) Unsaturated polyester resin Teletype, 8523, manufactured by Nippon U-Pica Co., Ltd. Unsaturated polyester resin 2: (A) Unsaturated polyester resin Isotype, 8510, manufactured by Nippon U-Pica Co., Ltd. Diallyl phthalate resin 1: DAP K, manufactured by Osaka Soda Co., Ltd. Hardener 1: Dicumyl peroxide, Percumyl D, NOF Corporation Filler 1: (B) Glass fiber, chopped strand, ECS03, Nippon Electric Glass Co., Ltd., average fiber diameter 11 μm Filler 2: Calcium carbonate, Tankal NS#100, manufactured by Nitto Funka Kogyo Co., Ltd. Flame retardant 1: (C) Aluminum hydroxide, C-308, manufactured by Sumitomo Chemical Co., Ltd., average particle size d 50 = 8 μm Flame retardant 2: Aluminum hydroxide, C-31, manufactured by Sumitomo Chemical Co., Ltd., average particle size d 50 = 50 μm Release agent 1: Calcium stearate, Ca-St, manufactured by Nitto Kasei Kogyo Co., Ltd. Pigment 1: Carbon black #750B, manufactured by Mitsubishi Chemical Corporation

[0035] (Mechanical strength) As an index of mechanical strength, the bending strength (MPa) was measured. Specifically, test pieces were prepared using a transfer molding machine (molding conditions: mold temperature 165°C; curing time 4 minutes) in accordance with JIS-K6911 "General testing method for thermosetting plastics," and the bending strength was measured. The results are shown in Table 1.

[0036] (Moisture resistance) As an index of moisture resistance, the change in mechanical strength when stored under high humidity conditions was measured. Specifically, for the molding materials obtained in each example, test pieces for evaluating moisture resistance were prepared according to the method for preparing test pieces in the measurement of "mechanical strength" described above. The obtained test pieces were stored in a thermohygrostat at 85°C and a relative humidity of 93% for 250 hours. The bending strength of the test pieces after storage was measured according to the above-mentioned method for measuring "mechanical strength". The results are also shown in Table 1.

[0037] (Flame resistance) As an index of flame resistance, a UL94 V flammability test was performed. Specifically, test pieces were prepared using a transfer molding machine (molding conditions: mold temperature 165°C; curing time 4 minutes) in accordance with the UL94 vertical flame resistance test, and flame resistance was measured. Those with a V-0 rating were deemed to have passed. The evaluation results are also shown in Table 1.

[0038] [Table 1]

[0039] As can be seen from Table 1, in each Example, the molded article obtained using the molding material had both good mechanical strength and good flame resistance. Moreover, as can be seen from Table 1, the molded articles obtained in each Example had excellent moisture resistance.

Claims

1. (A) an unsaturated polyester resin, (B) glass fibers, (C) aluminum hydroxide, Diallyl phthalate resin, and Carbon Black A molding material comprising: The content of the component (B) relative to 100 parts by mass of the resin in the molding material is 50 parts by mass or more and 150 parts by mass or less, The content of the component (C) relative to 100 parts by mass of the resin in the molding material is 100 parts by mass or more and 200 parts by mass or less, The content of the diallyl phthalate resin is 20 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the component (A), The average particle size d of the component (C) 50 The molding material has a particle size of 5 μm or more and 30 μm or less.

2. The molding material according to claim 1 , further comprising an inorganic filler other than the components (B) and (C).

3. 3. The molding material according to claim 1, wherein the component (A) is one or more phthalic acid-based unsaturated polyester resins selected from the group consisting of a teretype resin obtained by reacting terephthalic acid with a glycol and an isotype resin obtained by reacting isophthalic acid with a glycol.

4. 4. The molding material according to claim 1, further comprising one or more curing agents selected from the group consisting of peroxides.

Citation Information

Patent Citations

  • Unsaturated polyester resin molding compound

    JP2005239986A

  • Diallyl phthalate crosslinked low shrinkage unsaturated polyester resin composition for molding and molded article of the same

    JP2010202812A

  • Unsaturated polyester resin composition for LED reflector, and particulate, tablet, LED reflector, surface-mount type LED light-emitting device, and LED luminaire

    JP2013153144A

  • Unsaturated polyester resin composition and encapsulated motor

    WO2010150423A1